Geomorphological assessment on potential landslide hazard in the Ebbw Valley , Gwent, South Wales United Kingdom - Zulfahmi Ali Rahman (Universiti Kebangsaan Malaysia, 1999)
These works were carried out in order to collect the available information and to get general understanding upon the landslide occurrences and their characteristics. The landsliding problems in the South Wales are the main issue and being continually studied for minimizing the impact of coal mining activity and urbanization schemes. The preliminary study had been conducted and then followed by the preparation of the geomorphological maps of the study area in terms of their potential and contribution to the landslide problems. The landslide prone areas are closely related to the highly slope gradient ranging from 21º to over 35º and largely controlled by the geological underlying and human activity of coal mining along the valley flank. On the hilltop and valley side areas, the tension cracks have been gradually developed contributing to rockfalls largely influenced by the existing fault and joint structures. Evidences of mass movement comprise lobes of superficial deposits, rockfalls and coal fragments were found at the lower part of the valley areas. Water seeps through slope materials and being driven together to the toe of the slope.